PROBLEMS OF LOGISTIC OUTSOURCING AND ACCOUNTING OF SPECIFICS OF BUSINESS AT MAKING DECISION ON OUTSORCING - N. Barkova (Вестник университета)
Today logistics outsourcing is one of the most popular tools that allow companies to save costs. However, quite often companies that outsource logistics activities to thirdparty organizations observe deterioration in the quality of logistics operations. The problems and difficulties faced by companies applying for outsourcing, and identifies the causes of some problems has been analyzed. One of the reasons for dissatisfaction with the services of logistics outsourcing is the fact that companies providing outsourcing services do not sufficiently take into account the industry specifics of their client’s business and, using a standard approach, do not adjust their business processes to this specificity. A some of the characteristics of the business, which provide the prerequisites for outsourcing or insourcing logistics activities also has been highlighted.